ET PUIS DANS LES ÉNONCÉS NARRATIFS ET ARGUMENTATIFS UN EMBRAYEUR DU POINT DE VUE ET / OU UN CONNECTEUR ARGUMENTATIF - Chokri Rhibi (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2011)
This article is an investigation into some of the uses of the French temporal connector ‘puis’ ; usually translated as then in English. The article opens with a brief exposition of the temporal values of this connector. Then, the article seeks to show that in some contexts, especially when combined with the conjunction, this connector loses its temporal value and gains a rather argumentative one, and can thus be regarded as an indicator of point of view. Finally, the article attempts to shed light on the conditions that make such a shift possible.